Emergence of Distinct Salmonella enterica Serovar Enteritidis Lineage since 2020, South Korea - Eunkyung Shin; Tae-Min La; Jaeil Yoo; Junyoung Kim; Ji-Yeon Hyeon (Emerging Infectious Diseases)
We analyzed whole-genome sequences of Salmonella enterica serovar Enteritidis isolates in South Korea that had the SEGX01.049 pulsed-field gel electrophoresis pattern. That lineage has emerged and circulated in South Korea since 2020, leading to 2 fatal infection cases. We investigated the genomic characteristics and identified potential sources of that lineage. Isolates from outbreaks during 2020–2023 clustered in the Global IIa clade, along with other Salmonella Enteritidis strains from chicken farms in South Korea and human isolates from the United Kingdom. Bayesian molecular clock analysis estimated the time to the most recent common ancestor of our isolates in the Global IIa clade was 2017.57. Moreover, phylogeographic analysis supported substantial statistical evidence (Bayes factor 111.415; posterior probability 0.97) for the introduction of this lineage into South Korea from the United Kingdom. Continued genomic surveillance will be needed to monitor the spread of foodborne pathogens such as Salmonella Enteritidis and improve prevention strategies.